Terminalia arjuna bark extract improves diuresis and attenuates acute hypobaric hypoxia induced cerebral vascular leakage. (2nd March 2016) - Kumar, Kushal; Sharma, Sarika; Vashishtha, Vivek; Bhardwaj, Pushpender; Kumar, Ashish; Barhwal, Kalpana; Hota, Sunil Kumar; Malairaman, Udayabanu; Singh, Baljinder
Abstract: Ethnopharmacological relevance: Terminalia arjuna (Roxb. ex DC.) Wight & Arn. ( T. arjuna ) has been widely used in the traditional ayurvedic system of medicine as a cardioprotectant and for acute and chronic renal diseases supporting its ethnopharmacological use. Aim of the study: The present study aimed at evaluating the diuretic action of an alcoholic extract of T. arjuna and its possible use as a prophylactic to prevent vascular leakage during acute mountain sickness at high altitude. Materials and methods: Rats were exposed to hypobaric hypoxia simulated to an altitude of 27, 000 ft. in a decompression chamber for 12 h. T. arjuna bark extract was administered at a single dose of 150 mg/kg (p.o.) to male Sprague Dawley rats (200±20 g) 30 min prior to exposure. Total urine volume was measured during exposure to hypobaric hypoxia. The animals were then investigated for cerebral vascular leakage and serum concentration of sodium, potassium, renin, angiotensin-II, aldosterone and atrial natriuretic peptide (ANP). Results: T. arjuna ameliorated acute hypobaric hypoxia induced decrease in glomerular filtration rate ( p <0.5), increased total urine output ( p <0.5) and prevented cerebral vascular leakage in hypoxic rats. T. arjuna treated animals also showed decrease in serum levels of renin ( p <0.001) and angiotensin-II ( p <0.5) as compared to placebo treated animals. Administration of T. arjuna attenuated acute hypobaric hypoxia induced oxidative stress, improved aldosterone levels and altered electrolyte balance in animals through ANP dependent mechanism. Conclusion: Results of the present study indicate towards diuretic potential of hydro-alcoholic extract of T. arjuna bark and provide evidence for its novel application as a prophylactic to attenuate acute hypobaric hypoxia induced cerebral vascular leakage through ANP mediated modulation of renin-angiotensin-aldosterone system. Graphical abstract: